Identifying the important social outcomes for childhood cancer survivors: an e-Delphi study protocol. Issue 11 (21st November 2022) - Milner, Sarah; Feltbower, Richard G; Absolom, Kate; Glaser, Adam
Abstract : Introduction: Optimising the health of childhood cancer survivors is important given the high long-term survival rate coupled with a significant late effects burden. Included within the WHO's definition of 'Health' are social outcomes. These are of interest given their impact on adult functioning within society, complex interactions with physical and mental health outcomes and potential for cross generational effects. Categories included within the definition of social outcomes are ill defined leading to potential gaps in research and service provision which could affect the ability of survivors to achieve their maximal potential. An e-Delphi study will be used to achieve expert consensus on the most important social outcomes for childhood cancer survivors to inform future research and ultimately, service provision. Methods and analysis: A heterogeneous sample of at least 48 panel members will be recruited across four groups chosen to provide different perspectives on the childhood cancer journey: childhood cancer survivors, health professionals, social workers and teachers. Purposive sampling from a UK, regional long-term follow-up clinic will be used to recruit a representative sample of survivors. Other panel members will be recruited through local channels and national professional working groups. Opinions regarding breakdown and relevance of categories of social outcome will be collected through 3–5 rounds of questionnaires using an e-Delphi technique. Open ended, 7-point Likert scale and ranking questions will be used. Each round will be analysed collectively and per group to assess inter-rater agreement. Agreement and strength of agreement will be indicated by a median score of 6 or 7 and mean absolute deviation from the median, respectively. Ethics and dissemination: Ethical approval for this study has been granted by Regional Ethics Committee 4, West of Scotland (ID 297344). Study findings will be disseminated to involved stakeholders, published in a peer-reviewed journal and presented at conferences.